Fire Blight Susceptibility in Lilium spp. Correlates to Sensitivity to Botrytis elliptica Secreted Cell Death Inducing Compounds - Malvestiti, Michele C.; Immink, Richard G. H.; Arens, Paul; Quiroz Monnens, Thomas; van Kan, Jan A. L. (Frontiers in Plant Science, 2021)
Fire blight represents a widespread disease in Lilium spp. and is caused by the necrotrophic Ascomycete Botrytis elliptica. There are >100 Lilium species that fall into distinct phylogenetic groups and these have been used to generate the contemporary commercial genotypes. It is known among lily breeders and growers that different groups of lilies differ in susceptibility to fire blight, but the genetic basis and mechanisms of susceptibility to fire blight are unresolved. The aim of this study was to quantify differences in fire blight susceptibility between plant genotypes and differences in virulence between fungal isolates. To this end we inoculated, in four biological replicates over 2 years, a set of 12 B. elliptica isolates on a panel of 18 lily genotypes representing seven Lilium hybrid groups. A wide spectrum of variation in symptom severity was observed in different isolate-genotype combinations. There was a good correlation between the lesion diameters on leaves and flowers of the Lilium genotypes, although the flowers generally showed faster expanding lesions. It was earlier postulated that B. elliptica pathogenicity on lily is conferred by secreted proteins that induce programmed cell death in lily cells. We selected two aggressive isolates and one mild isolate and collected culture filtrate (CF) samples to compare the cell death inducing activity of their secreted compounds in lily. After leaf infiltration of the CFs, variation was observed in cell death responses between the diverse lilies. The severity of cell death responses upon infiltration of the fungal CF observed among the diverse Lilium hybrid groups correlated well to their fire blight susceptibility. These results support the hypothesis that susceptibility to fire blight in lily is mediated by their sensitivity to B. elliptica effector proteins in a quantitative manner. Cell death-inducing proteins may provide an attractive tool to predict fire blight susceptibility in lily breeding programs.